Implementasi Rapid Application Development dalam Pengembangan Aplikasi Pendaftaran Wisuda - Berliana Nafarita Hapshakh; Dwi Novia Prasetyanti; Prih Diantono Abda’u (Journal of Innovation Information Technology and Application (JINITA), 2021)
Graduation is an inauguration activity for students who have finished studying at a university. Graduation registration at the Cilacap State Polytechnic is still done conventionally, causing problems such as students who are not registered in the toga data collection, students who do not return the toga according to the specified time limit. In addition, the large number of students makes the data collection process take longer. In this case, the authors conducted research that aims to build a website-based graduation registration information system. Making this system requires a research methodology. Among them are data collection methods that include literature studies, observations, and interviews as well as the system development method used, namely Rapid Application Development (RAD). The results of the questionnaire with a total score of 182 show that the system is very good in assisting BAAK in graduation registration services and monitoring the number of graduates, as well as helping students register for graduation and their completeness, and the system can help submit and confirm trouble-free forms.